Propriedades estruturais e vibracionais dos pesticidas agrícolas carbaril e carbofurano: simulações computacionais no formalismo dft - Silva, Alexsandro Rocha da (2019)
Pesticides are one of the most representative groups of environmental pollutants due to their widespread use in agriculture. In Brazil, the agricultural pesticide market has grown approximately 176% in the last decade, being four times larger than the world average, becoming one of the world leaders in pesticide consumption. Carbaryl and carbofuran are pesticides from the cabamate group. Carbofuran (PubChem CID 2566) of molecular formula C12H15NO3 is a carbamate ester which is used as an insecticide, cupinicide, acaricide and nematicide. Carbaryl (PubChem CID 6129) of molecular formula C12H11NO2 is mainly used as an insecticide. They are derived from esters of carbamic acid CH3NO2 which is a highly unstable substance. In the present work, theoretical studies were made from molecular modeling of carbofuran and carbaryl pesticides aiming to obtain the structural and vibrational properties of these compounds. All calculations were performed using the Density Functional Theory (DFT), using the Becke hybrid functional Lee-Young-Par (B3LYP) and the 6-311+G(d,p) base set. Firstly, a Relaxed Scan on Potential Energy Surface (RPESS) was performed and then the lowest energy conformer was reoptimized. Finally, the normal modes of vibration were obtained and the notes made. Carbofuran and carbaryl presented one and two lower energy conformer, respectively. The infrared and Raman spectra of the carbine conformer presented very similar results